THE IMPACT OF COCONUT GROWING ON THE NATIONAL ECONOMY IN THE TURKISTAN ASSR AND THE UZBEKISTAN SSR IN 1920-1925 (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the impact of cocoon production on the national economy of the Turkestan ASSR and the Uzbek SSR during 1920–1925. The study examines the economic significance of sericulture, its role in the agricultural system, and the formation of production processes in this period. Particular attention is paid to the impact of cocoon production on employment, sources of income, and the export potential of the region. The article also evaluates the measures of Soviet economic policy aimed at developing the sector and their outcomes.
Keywords: cocoon production, sericulture, Turkestan ASSR, Uzbek SSR, national economy, agriculture, employment, export, economic policy, Soviet period.